2018
DOI: 10.1007/s11412-018-9283-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of two collaboration scripts on learning activities for wiki-based environments

Abstract: Knowledge construction assignments with wikis can be found in various educational settings. However, wiki environments are not inevitably suited to help learning and thus more guidance could be useful. In this study, we investigated the effects of two collaboration scripts with different aims during a two-week period of knowledge construction with wikis as a supplement to lectures about descriptive statistics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…In this light, scripting has been applied in various ways, and previous studies have indicated that the collaborative writing process can be facilitated by dividing it into particular phases and assigning students tasks or roles related to each phase in order to support the creation of a jointly written document (e.g. De Wever et al 2015;Heimbuch et al 2018). Additionally, scripting can be used to specify the roles that students are expected to adopt during collaboration processes or to trigger the roles that are relevant for high-level learning activities (e.g.…”
Section: Scripting As a Methods To Promote Students' Collaborationmentioning
confidence: 99%
“…In this light, scripting has been applied in various ways, and previous studies have indicated that the collaborative writing process can be facilitated by dividing it into particular phases and assigning students tasks or roles related to each phase in order to support the creation of a jointly written document (e.g. De Wever et al 2015;Heimbuch et al 2018). Additionally, scripting can be used to specify the roles that students are expected to adopt during collaboration processes or to trigger the roles that are relevant for high-level learning activities (e.g.…”
Section: Scripting As a Methods To Promote Students' Collaborationmentioning
confidence: 99%
“…In wikis, the behavioral challenge involves both contributing to filling the article with content and creating this content collaboratively and with adequate discussion. For this purpose, the discussion forum is suitable for exchanging opinions on the article topic before actual editing (Heimbuch et al, 2018). However, there is not always the willingness to exchange opinions in such environments Kreijns et al, 2013).…”
Section: Behavioral Challengementioning
confidence: 99%
“…Our study focuses on supporting the exchange in wiki discussion forums before article editing. It has already been shown that social interaction before actual article editing can be beneficial for both behavioral and cognitive outcomes (Heimbuch et al, 2018), leading to articles with fewer mistakes and enhanced learning potentials.…”
Section: Behavioral Challengementioning
confidence: 99%
See 2 more Smart Citations